Vitamin D in follicular development and oocyte maturation. Issue 6 (5th May 2021) - Xu, Fuhua; Wolf, Shally; Green, O'ryai; Xu, Jing
Abstract : Vitamin D (VD) is a secosteroid hormone synthesized predominantly in the skin upon UV light exposure, which can also be obtained from dietary sources. In target cells, the bioactive VD binds to specific VD receptor to regulate downstream transcription of genes that are involved in a wide range of cellular processes. There is an increasing recognition that the proper physiological levels of VD are critical for optimizing reproductive potential in women. The direct VD action in the ovary was first suggested in the 1980s. Since then, research has attempted to determine the role of VD in follicular development and oocyte maturation in animal models and clinical settings. However, data published to date are inconclusive due to the complexity in VD metabolism and the fact that VD actions are pervasive in regulating physiological functions in various systems, including the reproductive, endocrine and nervous systems that control reproduction. This review summaries in vitro, in vivo, and clinical evidence regarding VD metabolism and signaling in the ovary, as well as VD-regulated or VD-associated ovarian follicular development, steroidogenic function, and oocyte maturation. It is suggested that adequate animal models are needed for well-controlled studies to unravel molecular mechanisms of VD action in the ovary. For clinical studies, follicular development and function may be evaluated more effectively in a relatively homogeneous patient population under a well-controlled experimental design. A comprehensive understanding of VD-regulated folliculogenesis and oogenesis will provide critical insight into the impact of VD in female reproductive health.